Going batty - Krulik, Nancy E.; John & Wendy (New York : Grosset & Dunlap, 2009)
Fourth-grader Katie learns about nocturnal animals firsthand when the magic wind turns her into a bat during a class trip to the zoo.
Keywords: Bats -- Juvenile fiction; Nocturnal animals -- Juvenile fiction; Zoos -- Juvenile fiction; Magic -- Juvenile fiction